Manatee cognition and behavior: a neurobiological perspective on an unusual constellation of senses and a unique brain - Cook, Peter F.; Bauer, Gordon B.; Reep, Roger L. (Frontiers in Behavioral Neuroscience, 2025)
The nervous systems of manatees are strikingly unique across multiple dimensions. Manatees have the largest lissencephalic (smooth) brains in the animal kingdom, and demonstrate unusual somatosensory anatomy and physiology in the peripheral and central nervous system. As a rare aquatic herbivore sharing ancestry with modern elephants, manatee evolutionary history and behavioral ecology diverges substantially from that of other marine mammal clades, and their nervous system has adapted to the specific challenges they face. Although they are difficult to access for controlled behavioral study, prior neurobiological work has provided insight into manatee cognition. Here we review the evidence on manatee peripheral and central nervous function and present novel preliminary post-mortem diffusion MRI findings on whole-brain patterns of connectivity. Compared to another marine mammal, the California sea lion, manatee brains show apparently reduced corticocortical complexity. This may help explain their lissencephaly and relate to hypothesized reduced radial glial cell activity during neurodevelopment. Despite this apparently “simple” brain, manatees in the wild show some cognitively sophisticated behaviors, particularly in the realm of navigation. Future work in manatees should examine local and global brain connectivity related to spatial navigation and other complex cognitive capabilities.